Animal Models of Post‐Traumatic Stress Disorder. Issue 1 (15th July 2013) - Cohen, Hagit; Matar, Michael A.; Joseph, Zohar
Abstract: Animal behavioral studies have commonly regarded the entire group of animals subjected to the study conditions as homogeneous, disregarding individual differences in response patterns. The following discussion will focus on a method of analyzing data that aims to model clinical diagnostic criteria applied to individual patterns of response using data from behavioral measures, and employing cut‐off scores to distinguish between extremes of response versus non‐response and the sizeable proportion of study subjects in‐between them. This protocol unit will present the concept of the model and its background, provide detailed protocols for each of its components, and present a selection of studies employing and examining the model, alongside the underlying translational rationale of each. Curr. Protoc. Neurosci . 64:9.45.1‐9.45.18. © 2013 by John Wiley & Sons, Inc.